Energy storage and generation through desalination using flow-electrodes capacitive deionization - Lim, Hyunseung; Ha, Yuncheol; Jung, Hye Bin; Jo, Pil Sung; Yoon, Hana; Quyen, Do; Cho, Namchul; Yoo, Chung-Yul; Cho, Younghyun (Journal of industrial and engineering chemistry (Seoul, Korea), 2020)
Flow electrodes-based capacitive deionization (FCDI) is a highly energy-efficient desalination process compared to conventional processes, including reverse osmosis and multi-stage flash distillation. Furthermore, it provides a continuous desalination flow with high salt-removal capacity, whereas CDI using fixed electrodes requires additional electrode rinsing. In FCDI, salt ions are adsorbed onto flow carbon electrodes and stored in the electrode slurry container, which is similar to an electrochemical flow capacitor. Therefore, stored ions can generate energy during discharging in FCDI operation. In this study, such energy generation was systematically investigated in terms of the various discharging rates, feed concentrations, and volume of flow-electrode slurry. We found that the results were correlated with the changes in the salt concentration of the effluent flow. The discharging current of 50 mA showed the highest capacity for energy generation out of all the experimental conditions; it recovered around 25% of the energy consumed during FCDI desalination. We believe that such energy recovery can greatly reduce the energy consumption needed for FCDI desalination. Such recycling of generated energy would make FCDI more attractive than other conventional desalination techniques.